Understanding affective learning outcomes in entrepreneurship education - Sanna Ilonen; Jarna Heinonen (Sage, 2022)
In the field of entrepreneurship education (EE), researchers, educators and policy makers have long attempted to determine whether EE has an effect on students, and many studies have provided anecdotal evidence measuring the impacts of EE endeavours. There is a particular lack of understanding in relation to affective learning outcomes – that is, the beliefs, attitudes, impressions, desires, feelings, values, preferences and interests of students – and of the related indicators. In response to this lack of understanding, this study aims to identify students’ affective learning outcomes in EE based on a taxonomy of such outcomes (Krathwohl et al., 1964) and to investigate and understand in depth their nature. The study draws empirically on the learning reflections of university students enrolled on a Bachelor’s-level course on corporate entrepreneurship, which are qualitatively examined through thematic content analyses. The study identifies various external and internal affective learning outcomes based on the levels of expertise of students, and contributes to the existing EE literature by providing a more fine-grained understanding of these complex outcomes. For educators, the study makes affective learning visible in EE and provides insightful information for programme development.